Co-doped mechanoluminescent material, preparation method thereof, force-sensitive response household component and preparation method of force-sensitive response household component
By using a co-doped mechanoluminescent material Ca1-xLixZn0.98-xMn0.02NbxOS, the problems of weak luminescence intensity and high threshold of existing mechanoluminescent materials are solved, achieving a highly efficient force-sensitive response effect, which is suitable for smart home monitoring.
Patent Information
- Application Number
- CN202511065239.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-30
- Publication Date
- 2025-11-07
AI Technical Summary
Existing mechanoluminescent materials have weak luminescence intensity and transient emission, and a high mechanoluminescence threshold, which limits their application in applications with high sensor integration and large area.
A method for preparing co-doped mechanoluminescent material Ca1-xLixZn0.98-xMn0.02NbxOS was adopted. CaCO3, ZnS, MnCO3, Li2CO3 and Nb2O5 were mixed and calcined in a protective atmosphere. The calcination temperature and cooling rate were controlled to form a material with excellent mechanoluminescent properties. The material was then mixed with photosensitive resin and 3D printed to prepare force-sensitive home furnishing parts.
It significantly improves the mechanoluminescence intensity and reduces the mechanoluminescence threshold, enabling force-sensitive intelligent monitoring in different scenarios. In particular, when the Li and Nb doping concentration is 0.05%, the mechanoluminescence intensity is increased by 34.6 times, making it suitable for future smart home monitoring components.
Smart Images

Figure CN120904886A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of mechanoluminescent materials, in particular to a co-doped mechanoluminescent material and a preparation method thereof, and a force-sensitive response home component and a preparation method thereof. BACKGROUND
[0002] A new round of technological revolution led by artificial intelligence, 5G communication, Internet of Things and biotechnology is accelerating the impact on human life, and advanced intelligent mechanical sensors have attracted extensive attention of researchers in the fields of wearable devices, robots, flexible electronic devices, etc. For traditional electric signal collection methods, when the sensor integration is high and the area is large, point-by-point collection of electric signals not only requires a long time, but also needs a complex connection line structure, which limits its application in certain occasions. Giving the sensing element the property of mechanoluminescence can change the detection from collecting electric signals to detecting the change of visible light intensity or color, which can greatly simplify the structure of the sensor connection line and reduce the signal collection time, and provides the possibility for high-speed parallel pressure distribution collection.
[0003] At present, the luminous intensity of most mechanoluminescent materials is still weak, and the luminescence is instantaneous, and the mechanoluminescence threshold is high. SUMMARY
[0004] The present application provides a co-doped mechanoluminescent material and a preparation method thereof, and a force-sensitive response home component and a preparation method thereof, the co-doped mechanoluminescent material of the present application has high luminous intensity and low mechanoluminescence threshold.
[0005] The present application provides a co-doped mechanoluminescent material, the chemical formula of the co-doped mechanoluminescent material is Ca 1-x Li x Zn 0.98-x Mn 0.02 Nb x OS, 0
[0006] Preferably, the x is 0.02, 0.05 or 0.1.
[0007] The present application also provides a preparation method of the co-doped mechanoluminescent material according to the above technical solution, comprising the following steps:
[0008] CaCO3, ZnS, MnCO3, Li2CO3 and Nb2O5 are mixed to obtain a mixture;
[0009] The mixture is calcined to obtain the co-doped mechanoluminescent material;
[0010] The molar ratio of Ca element, Li element, Zn element, Mn element and Nb element in the mixture is (1-x):x:(0.98-x):0.02:x, 0
[0011] Preferably, the mixing comprises: mixing CaCO3, ZnS, MnCO3, Li2CO3, Nb2O5 with ethanol and then grinding to dry state.
[0012] Preferably, the calcination temperature is 1050-1150℃, and the holding time is 3.5-4.5h.
[0013] The calcination is carried out in a protective atmosphere.
[0014] Preferably, the temperature rising to the calcination temperature comprises: rising the temperature to 900-1000℃ at a temperature rising rate of 6-8℃ / min, and then rising the temperature to 1050-1150℃ at a temperature rising rate of 3-5℃ / min.
[0015] Preferably, after the calcination, the method further comprises: cooling the obtained calcination product.
[0016] The cooling comprises: cooling to 900-1000℃ at a temperature falling rate of 3-5℃ / min, and then cooling to 500-650℃ at a temperature falling rate of 6-8℃ / min, and then naturally cooling to room temperature.
[0017] The application also provides a force-sensitive response home component, and the preparation raw material of the force-sensitive response home component comprises a photosensitive resin and a co-doped mechanoluminescent material; the co-doped mechanoluminescent material is the co-doped mechanoluminescent material in the above technical solution or the co-doped mechanoluminescent material prepared by the preparation method in the above technical solution.
[0018] The mass ratio of the co-doped mechanoluminescent material and the photosensitive resin is 1:5-15.
[0019] Preferably, the photosensitive resin comprises 3D Printer UVCurable Resin Standard Resin Plus of Shenzhen Chuangxi Sanji Sci-Tech Co., Ltd.
[0020] The application also provides a preparation method of the force-sensitive response home component in the above technical solution, and the preparation method comprises the following steps.
[0021] Mixing the preparation raw material of the force-sensitive response home component according to a preset model to perform 3D printing to obtain a green body.
[0022] Photocuring the green body to obtain the force-sensitive response home component.
[0023] The application introduces Li elements and Nb elements into CaZn 0.98 Mn 0.02 The OS mechanoluminescent material introduces Li elements and Nb elements, and forms a co-doped mechanoluminescent material with excellent mechanoluminescent performance. Compared with most existing mechanoluminescent materials, the co-doped mechanoluminescent material has significantly improved mechanoluminescent intensity and a lower mechanoluminescent threshold. In particular, when the Li and Nb doping concentrations are 0.05, compared with non-co-doping, the intensity can be increased by 34.6 times when an external force of 0.2N is applied.
[0024] The co-doped mechanoluminescent material of the application is 3D printed, and the 3D printed stair and floor model parts have strong mechanoluminescence in bright and dark environments. The preparation method has mild conditions, is simple and easy to operate, and has low cost, and can be widely applied to future home scene force-sensitive intelligent monitoring parts. BRIEF DESCRIPTION OF DRAWINGS
[0025] Figure 1 X-ray diffraction patterns of the mechanoluminescent materials prepared in Examples 1-3 and Comparative Examples 1-3;
[0026] Figure 2 Variation of the mechanoluminescent intensity of the mechanoluminescent materials of Examples 1-3 and Comparative Example 1 under 15N with different co-doping concentrations;
[0027] Figure 3 Variation of the mechanoluminescent intensity of the mechanoluminescent materials of Examples 1-3 and Comparative Example 1 under 10N with different co-doping concentrations;
[0028] Figure 4 Variation of the mechanoluminescent intensity of the mechanoluminescent materials of Examples 1-3 and Comparative Example 1 under 5N with different co-doping concentrations;
[0029] Figure 5 Variation of the mechanoluminescent intensity of the mechanoluminescent materials of Examples 1-3 and Comparative Example 1 under 1N with different co-doping concentrations;
[0030] Figure 6 Variation of the mechanoluminescent intensity of the mechanoluminescent materials of Examples 1-3 and Comparative Example 1 under 0.2N with different co-doping concentrations;
[0031] Figure 7 Variation of the mechanoluminescent intensity of the mechanoluminescent materials of Examples 2 and Comparative Examples 2-3 under 15N with different co-doping concentrations;
[0032] Figure 8 Variation of the mechanoluminescent intensity of the mechanoluminescent materials of Examples 2 and Comparative Examples 2-3 under 10N with different co-doping concentrations;
[0033] Figure 9The piezoluminescence intensity of the piezoluminescence material of Example 2 and Comparative Examples 2-3 changes with different concentrations of co-doping under 5N;
[0034] Figure 10 The piezoluminescence intensity of the piezoluminescence material of Example 2 and Comparative Examples 2-3 changes with different concentrations of co-doping under 1N;
[0035] Figure 11 The piezoluminescence intensity of the piezoluminescence material of Example 2 and Comparative Examples 2-3 changes with different concentrations of co-doping under 0.2N;
[0036] Figure 12 The intensity ratio of the piezoluminescence intensity of the piezoluminescence material of Examples 1-3 to the piezoluminescence intensity of the piezoluminescence material of Comparative Example 1 under 15N, 10N, 5N, 1N and 0.2N, and the intensity ratio of the piezoluminescence intensity of the piezoluminescence material of Example 2 to the piezoluminescence intensity of the piezoluminescence material of Comparative Examples 2-3;
[0037] Figure 13 The 3D printed stair model part of Application Example 1 and the piezoluminescence test results;
[0038] Figure 14 The 3D printed floor model part of Application Example 2 and the piezoluminescence test results. DETAILED DESCRIPTION
[0039] The present application provides a co-doped piezoluminescence material, the chemical formula of the co-doped piezoluminescence material is Ca 1-x Li x Zn 0.98-x Mn 0.02 Nb x OS, 0 < x ≤ 0.1.
[0040] In the present application, the x can be 0.02, 0.05 or 0.1.
[0041] The present application also provides a preparation method of the co-doped piezoluminescence material of the above technical solution, comprising the following steps:
[0042] CaCO3, ZnS, MnCO3, Li2CO3 and Nb2O5 are mixed to obtain a mixture;
[0043] The mixture is calcined to obtain the co-doped piezoluminescence material;
[0044] The amount-of-substance ratio of Ca element, Li element, Zn element, Mn element and Nb element in the mixture is (1-x):x:(0.98-x):0.02:x, 0 < x ≤ 0.1.
[0045] The CaCO3, ZnS, MnCO3, Li2CO3 and Nb2O5 are mixed to obtain a mixture.
[0046] In the present application, the mixing preferably comprises: grinding CaCO3, ZnS, MnCO3, Li2CO3, Nb2O5 to dry state after mixing with ethanol.
[0047] The amount of ethanol used in the present application is not particularly limited, and the CaCO3, ZnS, MnCO3, Li2CO3 and Nb2O5 can be covered.
[0048] The grinding method is preferably hand grinding.
[0049] The use of ethanol as a grinding medium is based on its volatile medium, safe and non-toxic characteristics, and the use of ethanol as a medium can also improve the dispersibility of carbonates and oxides during hand grinding, which is beneficial to the full mixing of materials.
[0050] After obtaining the mixture, the present application calcines the mixture to obtain the co-doped mechanoluminescent material.
[0051] In the present application, the calcination is preferably carried out in a protective atmosphere, the temperature of the calcination is preferably 1050-1150℃, the holding time is preferably 3.5-4.5h, and the temperature rising to the calcination temperature preferably comprises: rising to 900-1000℃ at a temperature rising rate of 6-8℃ / min, and then rising to 1050-1150℃ at a temperature rising rate of 3-5℃ / min.
[0052] After the calcination, the present application preferably further comprises: cooling the obtained calcination product; the preferred cooling comprises: cooling to 900-1000℃ at a temperature falling rate of 3-5℃ / min, and then cooling to 500-650℃ at a temperature falling rate of 6-8℃ / min, and then naturally cooling to room temperature.
[0053] The present application obtains a co-doped mechanoluminescent material with excellent mechanoluminescent performance by controlling the calcination temperature, temperature rising rate and temperature falling rate.
[0054] The present application also provides a force-sensitive response home component, the preparation raw material of the force-sensitive response home component comprises a photosensitive resin and a co-doped mechanoluminescent material; the co-doped mechanoluminescent material is the co-doped mechanoluminescent material described in the above technical solution or the co-doped mechanoluminescent material prepared by the preparation method described in the above technical solution; the mass ratio of the co-doped mechanoluminescent material and the photosensitive resin is 1:5-15.
[0055] In the present application, the photosensitive resin preferably comprises 3D Printer UV Curable Resin Standard Resin Plus of Shenzhen Chuangxi Sanzhong Technology Co., Ltd.
[0056] The present application also provides a preparation method of the force-sensitive response home component, comprising the following steps:
[0057] Mixing the preparation raw materials of the force-sensitive response home component according to the preset model to perform 3D printing to obtain a blank;
[0058] Photocuring the blank to obtain the force-sensitive response home component.
[0059] The present application mixes the preparation raw materials of the force-sensitive response home component according to the preset model to perform 3D printing to obtain a blank.
[0060] In the present application, the preset model is preferably obtained by drawing with HALOT BOX software.
[0061] The 3D printing is preferably further leveled before the 3D printing.
[0062] The 3D printing preferably further comprises cleaning the obtained model to obtain the blank.
[0063] The cleaning agent used for cleaning preferably comprises ethanol.
[0064] After obtaining the blank, the present application photocures the blank to obtain the force-sensitive response home component.
[0065] In the present application, the wavelength of photocuring is preferably 405 nm, and the time is preferably 5 min.
[0066] The co-doped force-induced luminescent material and the preparation method thereof, the force-sensitive response home component and the preparation method thereof provided by the present application will be described in detail below in combination with embodiments, but they should not be understood as limiting the protection scope of the present application.
[0067] CaCO3National Pharmaceutical Group Chemical Reagent Co., Ltd. ≥99.0%
[0068] ZnS Shanghai Maier Chemical Reagent Co., Ltd. 99.99%
[0069] MnCO3Aladdin Reagent (Shanghai) Co., Ltd. 99.95%
[0070] Li2CO3Aladdin Reagent (Shanghai) Co., Ltd. 99.99%
[0071] Nb2O5Aladdin Reagent (Shanghai) Co., Ltd. 99.99%
[0072] 3D Printer UV Curable Resin Standard Resin Plus Shenzhen Chuangxi 3D Technology Co., Ltd. Density is 1.14 g / cm 3
[0073] Example 1
[0074] A chemical formula is Ca 0.98 Li 0.02 Zn 0.96 Mn 0.02 Nb 0.02 The specific preparation steps of the co-doped electroluminescent material of OS are as follows:
[0075] S1, CaCO3, ZnS, MnCO3, Li2CO3, Nb2O5 are placed in a mortar for hand grinding to obtain a mixture, and the amount-of-substance ratio of elements Ca, Li, Zn, Mn, Nb in the mixture is 0.98:0.02:0.96:0.02:0.02. Hand grinding for 1h to dry state, the medium is anhydrous ethanol, and the amount added needs to cover all the powders;
[0076] S2, the mixture obtained in S1 is placed in an alumina square canister, in a tube furnace, nitrogen is passed, the temperature is raised to 1000℃ at a rate of 8℃ / min, then the temperature is raised to 1100℃ at a rate of 4℃ / min, and calcined for 4h. Then, the temperature is lowered to 1000℃ at a rate of 4℃ / min, then the temperature is lowered to 550℃ at a rate of 8℃ / min, and cooled to room temperature naturally.
[0077] S3, the precursor obtained in S2 is transferred to a mortar for grinding to a finer powder until no obvious particle feeling is felt, that is, Ca 0.98 Li 0.02 Zn 0.96 Mn 0.02 Nb 0.02 OS powder is obtained.
[0078] Example 2
[0079] A chemical formula is Ca 0.95 Li 0.05 Zn 0.93 Mn 0.02 Nb 0.05 The specific preparation steps of the co-doped electroluminescent material of OS are as follows:
[0080] S1, CaCO3, ZnS, MnCO3, Li2CO3, Nb2O5 were placed in a mortar for hand grinding to obtain a mixture, the molar ratio of elements Ca, Li, Zn, Mn, Nb in the mixture was 0.95:0.05:0.93:0.02:0.05. Hand grinding for 1h to dry state, the medium was anhydrous ethanol, and the amount of the medium should cover all the powders;
[0081] S2, the mixture obtained in S1 was placed in an alumina tank, in a tube furnace, nitrogen was passed, the temperature was raised to 1000℃ at a rate of 8℃ / min, then the temperature was raised to 1100℃ at a rate of 4℃ / min, and calcined for 4h. Then the temperature was lowered to 1000℃ at a rate of 4℃ / min, and then the temperature was lowered to 550℃ at a rate of 8℃ / min.
[0082] S3, the precursor obtained in S2 was transferred to a mortar for grinding to a finer powder until no obvious particles were felt, i.e. Ca 0.95 Li 0.05 Zn 0.93 Mn 0.02 Nb 0.05 OS powder was obtained.
[0083] Example 3
[0084] A co-doped mechanoluminescent material of chemical formula Ca 0.90 Li 0.10 Zn 0.88 Mn 0.02 Nb 0.10 OS, the specific preparation steps are as follows:
[0085] S1, CaCO3, ZnS, MnCO3, Li2CO3, Nb2O5 were placed in a mortar for hand grinding to obtain a mixture, the molar ratio of elements Ca, Li, Zn, Mn, Nb in the mixture was 0.90:0.10:0.88:0.02:0.10. Hand grinding for 1h to dry state, the medium was anhydrous ethanol, and the amount of the medium should cover all the powders;
[0086] S2, the mixture obtained in S1 was placed in an alumina tank, in a tube furnace, nitrogen was passed, the temperature was raised to 1000℃ at a rate of 8℃ / min, then the temperature was raised to 1100℃ at a rate of 4℃ / min, and calcined for 4h. Then the temperature was lowered to 1000℃ at a rate of 4℃ / min, and then the temperature was lowered to 550℃ at a rate of 8℃ / min.
[0087] S3, the precursor obtained in S2 was transferred to a mortar for grinding to a finer powder until no obvious particles were felt, i.e. Ca 0.90 Li 0.10 Zn0.88 Mn 0.02 Nb 0.10 OS powder.
[0088] Comparative Example 1
[0089] A chemical formula is CaZn 0.98 Mn 0.02 OS, the specific preparation steps are as follows:
[0090] S1, CaCO3, ZnS, MnCO3 are placed in a mortar for hand grinding to obtain a mixture, the mass ratio of elements Ca, Zn, Mn in the mixture is 1:0.98:0.02. Hand grinding for 1h to dry state, the medium is anhydrous ethanol, and the amount added needs to cover all the powders;
[0091] S2, the mixture obtained in S1 is placed in an alumina tank in a tube furnace, nitrogen is passed, the temperature is raised to 1000℃ at a rate of 8℃ / min, then the temperature is raised to 1100℃ at a rate of 4℃ / min, and calcined for 4h. Then the temperature is lowered to 1000℃ at a rate of 4℃ / min, then the temperature is lowered to 550℃ at a rate of 8℃ / min, and cooled to room temperature naturally.
[0092] S3, the precursor obtained in S2 is transferred to a mortar for grinding to a finer powder until no obvious particle feeling is felt, that is, CaZn 0.98 Mn 0.02 OS powder.
[0093] Comparative Example 2
[0094] A chemical formula is Ca 0.95 Li 0.05 Zn 0.98 Mn 0.02 OS co-doped mechanoluminescence material, the specific preparation steps are as follows:
[0095] S1, CaCO3, ZnS, MnCO3, Li2CO3 are placed in a mortar for hand grinding to obtain a mixture, the mass ratio of elements Ca, Li, Zn, Mn in the mixture is 0.95:0.05:0.98:0.02. Hand grinding for 1h to dry state, the medium is anhydrous ethanol, and the amount added needs to cover all the powders;
[0096] S2, the mixture obtained in S1 is placed in an alumina tank in a tube furnace, nitrogen is passed, the temperature is raised to 1000℃ at a rate of 8℃ / min, then the temperature is raised to 1100℃ at a rate of 4℃ / min, and calcined for 4h. Then the temperature is lowered to 1000℃ at a rate of 4℃ / min, then the temperature is lowered to 550℃ at a rate of 8℃ / min.
[0097] S3, the precursor obtained in S2 is transferred to a mortar and ground into a finer powder until no obvious particles are felt, i.e., Ca 0.95 Li 0.05 Zn 0.98 Mn 0.02 OS powder.
[0098] Comparative Example 3
[0099] A CaZn 0.93 Mn 0.02 Nb 0.05 OS co-doped mechanoluminescent material, the specific preparation steps are as follows:
[0100] S1, CaCO3, ZnS, MnCO3, and Nb2O5 are placed in a mortar and hand-ground to obtain a mixture, the mass ratio of elements Ca, Zn, Mn, and Nb in the mixture is 1:0.93:0.02:0.05. Hand grinding is performed for 1 h to a dry state, the medium is anhydrous ethanol, and the amount of the medium needs to cover all the powders;
[0101] S2, the mixture obtained in S1 is placed in an alumina canister, and is heated in a tube furnace with nitrogen, at a heating rate of 8 ℃ / min to 1000 ℃, then at a heating rate of 4 ℃ / min to 1100 ℃, and calcined for 4 h. Then, at a cooling rate of 4 ℃ / min to 1000 ℃, then at a cooling rate of 8 ℃ / min to 550 ℃.
[0102] S3, the precursor obtained in S2 is transferred to a mortar and ground into a finer powder until no obvious particles are felt, i.e., CaZn 0.93 Mn 0.02 Nb 0.05 OS powder.
[0103] Application Example 1
[0104] A CaZn 0.98 Mn 0.02 OS co-doped mechanoluminescent material with excellent performance 0.95 Li 0.05 Zn 0.93 Mn 0.02 Nb 0.05 OS 3D printed force-sensitive response stair part, the specific preparation steps are as follows:
[0105] S1, a printing stair model is constructed according to experimental requirements, a drawing is made by HALOT BOX software, the weight of the printing material required is estimated according to the size of the stair model, and the instrument is leveled. It needs to be noted that the instrument needs to be leveled again before each sample is printed.
[0106] S2, the force luminescent material Ca 0.95 Li 0.05 Zn 0.93 Mn 0.02 Nb 0.05 OS and photosensitive resin (3D Printer UVCurable Resin Standard Resin Plus) were placed in a beaker in a mass ratio of 1:10, a rotor was added, and stirring was carried out on a magnetic stirrer. The stirring time was 20 mins.
[0107] S3, pour the mixture obtained in S2 into the trough, start pouring from the middle of the trough, and pour until the mixture is evenly spread.
[0108] S4, connect the instrument with a U disk, find the stair model file, slice (see parameters), and then start printing the stair model.
[0109] S5, place the stair model printed in S4 in the cleaning tank for cleaning, use 95% or more alcohol for cleaning (do not overflow the cleaning tank), cover the lid during cleaning, and the cleaning time is 5 mins.
[0110] S6, take out the stair model cleaned in S5 from the cleaning tank, place it in a white tray, align the slot and put it into the cleaner, do not press hard, cover the outer cover, and cure under the light with a wavelength of 405 nm for 5 mins.
[0111] Application Example 2
[0112] A CaZn 0.98 Mn 0.02 OS-based co-doped force luminescent material Ca 0.95 Li 0.05 Zn 0.93 Mn 0.02 Nb 0.05 OS 3D printed force-sensitive response floor component, the specific preparation steps are as follows:
[0113] S1, construct a printed floor model according to experimental requirements, draw a graph with HALOT BOX software, estimate the weight of the required printing material according to the size of the floor model, and level the instrument. It needs to be noted that each sample needs to be leveled again before printing.
[0114] S2, the force luminescent material Ca 0.95 Li 0.05 Zn 0.93 Mn 0.02 Nb 0.05OS and photosensitive resin (3D Printer UVCurable Resin Standard Resin Plus) were placed in a beaker in a mass ratio of 1:10, a rotor was added, and stirring was performed on a magnetic stirrer. The stirring time was 20 mins.
[0115] S3, pour the mixture obtained in S2 into the trough, start pouring from the middle of the trough, and pour until the mixture is evenly spread.
[0116] S4, connect the instrument using a U disk, find the floor model file, slice (see parameters), and then start printing the floor model.
[0117] S5, place the floor model printed in S4 in the cleaning tank for cleaning, use 95% or more alcohol for cleaning (do not overflow the cleaning tank), cover the lid during cleaning, and the cleaning time is 5 mins.
[0118] S6, take out the floor model cleaned in S5 from the cleaning tank and place it in a white tray, align the card slot and put it into the cleaner, do not press hard, cover the outer cover, and cure under the light with a wavelength of 405 nm for 5 mins.
[0119] Performance test:
[0120] (I) X-ray diffraction experiment:
[0121] The piezoluminescent materials prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to X-ray diffraction test to obtain the XRD patterns of the materials.
[0122] Figure 1 X-ray diffraction patterns of the piezoluminescent materials prepared in Examples 1-3 and Comparative Examples 1-3. Figure 1 Medium (N) = 0.05 represents CaZnOS of Comparative Example 3 0.93 Mn 0.02 Nb 0.05 OS, Figure 1 Medium (L) = 0.05 represents Ca 0.95 Li 0.05 Zn 0.98 Mn 0.02 OS.
[0123] The XRD results show that the synthesized Ca 1-x Li x Zn 0.98-x Mn 0.02 Nb x OS (0 < x ≤ 0.1) is mainly composed of CaZnOS.
[0124] (II) Piezoluminescent performance test
[0125] The plastic packaging film is fixed on the test device, and the push-pull force meter with the test end of the optical fiber is fixed on the plastic packaging film to test the starting position. The required force is added, and the force-induced luminescence test is carried out in a dark environment. Change the applied force, and compare the force-induced luminescence intensity of the co-doped sample and the non-co-doped sample under different forces.
[0126] Figures 2-6 The force-induced luminescence intensity of the force-induced luminescence material of Examples 1-3 and Comparative Example 1 changes with different concentrations of co-doping under 15N, 10N, 5N, 1N, 0.2N, respectively: Figure 2 The force-induced luminescence intensity of the force-induced luminescence material of Examples 1-3 and Comparative Example 1 changes with different concentrations of co-doping under 15N, 10N, 5N, 1N, 0.2N, respectively: Figure 3 The force-induced luminescence intensity of the force-induced luminescence material of Examples 1-3 and Comparative Example 1 changes with different concentrations of co-doping under 15N, 10N, 5N, 1N, 0.2N, respectively: Figure 4 The force-induced luminescence intensity of the force-induced luminescence material of Examples 1-3 and Comparative Example 1 changes with different concentrations of co-doping under 15N, 10N, 5N, 1N, 0.2N, respectively: Figure 5 The force-induced luminescence intensity of the force-induced luminescence material of Examples 1-3 and Comparative Example 1 changes with different concentrations of co-doping under 15N, 10N, 5N, 1N, 0.2N, respectively: Figure 6 The force-induced luminescence intensity of the force-induced luminescence material of Examples 1-3 and Comparative Example 1 changes with different concentrations of co-doping under 15N, 10N, 5N, 1N, 0.2N, respectively:
[0127] From Figures 2-6 It can be concluded that when the concentration of co-doped Li and Nb is 0.05, the force-induced luminescence intensity under different forces is stronger than that of non-co-doped, and the force-induced luminescence intensity is the strongest. When the concentration of co-doped Li and Nb is 0.02, the force-induced luminescence intensity under different forces is also stronger than that of non-co-doped, but the force-induced luminescence intensity is weaker than that of co-doped Li and Nb with a concentration of 0.05. When the concentration of co-doped Li and Nb is 0.1, the force-induced luminescence intensity under 1N and 0.2N is stronger than that of non-co-doped.
[0128] Figures 7-11 The force-induced luminescence intensity of the force-induced luminescence material of Examples 1-3 and Comparative Example 1 changes with different concentrations of co-doping under 15N, 10N, 5N, 1N, 0.2N, respectively: Figures 7-11 N) = 0.05 represents the CaZn of Comparative Example 3 0.93 Mn 0.02 Nb 0.05 OS, (L) = 0.05 represents the Ca of Comparative Example 2 0.95 Li 0.05 Zn 0.98 Mn 0.02 OS, (LN) = 0.05 represents the Ca of Example 2 0.95 Li 0.05 Zn 0.93 Mn0.02 Nb 0.05 OS: Figure 7 The piezoluminescence intensity of the piezoluminescence material of Example 2, Comparative Examples 2-3 changes with different concentrations of co-doping under 15N; Figure 8 The piezoluminescence intensity of the piezoluminescence material of Example 2, Comparative Examples 2-3 changes with different concentrations of co-doping under 10N; Figure 9 The piezoluminescence intensity of the piezoluminescence material of Example 2, Comparative Examples 2-3 changes with different concentrations of co-doping under 5N; Figure 10 The piezoluminescence intensity of the piezoluminescence material of Example 2, Comparative Examples 2-3 changes with different concentrations of co-doping under 1N; Figure 11 The piezoluminescence intensity of the piezoluminescence material of Example 2, Comparative Examples 2-3 changes with different concentrations of co-doping under 0.2N.
[0129] From Figures 7-11 It can be concluded that when the concentration of co-doped Li and Nb is 0.05, the piezoluminescence intensity under different forces is stronger than that of single-doped Li with a concentration of 0.05 and single-doped Nb with a concentration of 0.05, and the piezoluminescence intensity of single-doped Li is stronger than that of single-doped Nb.
[0130] Figure 12 The intensity ratio of the piezoluminescence intensity of the piezoluminescence material of Examples 1-3 compared to the piezoluminescence intensity of the piezoluminescence material of Comparative Example 1 under 15N, 10N, 5N, 1N, 0.2N, and the intensity ratio of the piezoluminescence intensity of the piezoluminescence material of Example 2 compared to the piezoluminescence intensity of the piezoluminescence material of Comparative Examples 2-3. It can be clearly seen that the intensity ratio gradually increases with the decrease of force, and when the concentration of co-doped Li and Nb is 0.05 and 0.02, the ratio under 0.2N reaches 34.6 and 28.9 respectively.
[0131] (Three) 3D printed model part piezoluminescence test
[0132] The 3D printed stair model part prepared in Application Example 1 was subjected to piezoluminescence test, and the 3D printed stair model part was drawn with a glass rod in bright and dark environments respectively, and the luminescence was observed.
[0133] Figure 13 The 3D printed model part of Application Example 1 and the piezoluminescence test results are as follows: Figure 13 In (a), the 3D printed stair model part is shown, Figure 13 In (b), the piezoluminescence photo of the model part in bright environment, Figure 13 In (c), the piezoluminescence photo of the model part in dark environment.
[0134] The 3D printed floor model part prepared in application example 2 was subjected to force-induced luminescence test, and the 3D printed floor model part was scratched with a glass rod in bright and dark environments respectively, and the luminescence was observed.
[0135] Figure 14 The 3D printed floor model part prepared in application example 2 was subjected to force-induced luminescence test, and the 3D printed floor model part was scratched with a glass rod in bright and dark environments respectively, and the luminescence was observed. Figure 14 Fig. (a) is a schematic diagram of the 3D printed floor model part, Figure 14 Fig. (b) is a photo of the model part force-induced luminescence in bright environment, Figure 14 Fig. (c) is a photo of the model part force-induced luminescence in dark environment.
[0136] It can be seen that the stair and floor model parts have strong luminescence in bright and dark environments, and can be widely applied to force-sensitive intelligent monitoring parts in different scenes of future home.
[0137] The above only describes the preferred embodiments of the present application, and it should be noted that for those skilled in the art, without departing from the principles of the present application, a number of improvements and refinements can be made, and these improvements and refinements should also be considered as the protection scope of the present application.
Claims
1. A co-doped mechanoluminescent material, characterized in that, The chemical formula of the co-doped mechanoluminescent material is Ca 1- x Li x Zn 0.98-x Mn 0.02 Nb x OS, 0 < x ≤ 0.
1.
2. The co-doped mechanoluminescent material of claim 1, wherein, The x is 0.02, 0.05 or 0.
1.
3. A method for producing the co-doped mechanoluminescent material according to claim 1 or 2, characterized by, The method comprises the following steps: CaCO3, ZnS, MnCO3, Li2CO3 and Nb2O5 are mixed to obtain a mixture; The mixture is calcined to obtain the co-doped mechanoluminescent material; The molar ratio of Ca element, Li element, Zn element, Mn element and Nb element in the mixture is (1-x):x:(0.98-x):0.02:x, 0 4. The production method according to claim 3, characterized by, The mixing comprises: mixing CaCO3, ZnS, MnCO3, Li2CO3, Nb2O5 and ethanol, and then grinding to dryness.
5. The preparation method according to claim 3, characterized in that, The calcination temperature is 1050-1150℃, and the holding time is 3.5-4.5h; The calcination is carried out in a protective atmosphere.
6. The preparation method according to claim 5, characterized in that, The temperature rising to the calcination temperature comprises: rising the temperature to 900-1000℃ at a temperature rising rate of 6-8℃ / min, and then rising the temperature to 1050-1150℃ at a temperature rising rate of 3-5℃ / min.
7. The production method according to claim 5 or 6, characterized by, After the calcination, the method further comprises: cooling the obtained calcination product; The cooling comprises: cooling the temperature to 900-1000℃ at a temperature falling rate of 3-5℃ / min, and then cooling the temperature to 500-650℃ at a temperature falling rate of 6-8℃ / min, and then naturally cooling to room temperature.
8. A force sensitive responsive home component, characterized in that, The preparation raw material of the force-sensitive response home component comprises a photosensitive resin and a co-doped mechanoluminescent material; the co-doped mechanoluminescent material is the co-doped mechanoluminescent material of claim 1 or 2 or the co-doped mechanoluminescent material prepared by the preparation method of any one of claims 3-7. The mass ratio of the co-doped mechanoluminescent material and the photosensitive resin is 1:5-15.
9. The force-sensitive responsive home component of claim 8, wherein, The photosensitive resin comprises 3D Printer UV Curable Resin Standard Resin Plus of Shenzhen Chuangxi Sanji Sci-Tech Co., Ltd.
10. The method of producing a force-sensitive responsive home component according to claim 8 or 9, characterized in that The method comprises the following steps: The preparation raw material of the force-sensitive response home component is mixed according to a preset model to carry out 3D printing to obtain a blank; The blank is subjected to photocuring to obtain the force-sensitive response home component.